معاصر معاشرتی مسائل اور اردوتفاسیر:عبد المجید لدھیانوی کی "تبیان الفرقان" کا مطالعہContemporary Social Issues and Urdu Tafāsīr: A Study of Mawlānā Abdul Majeed Ludhiānvī’s "Tibyān al-Furqān" (Al-Qamar, 2020)
This article studies the interpretive efforts of Mawlānā Abdul Majeed Ludhiānvī (1934-2015), a Pakistani Islamic scholar and commentator of the Quran, regarding some important contemporary social issues like friendship with non-Muslims, the need for marriage, sitting in assemblies of the opponents of Islam, killing of children in the pre-Islamic era and the contemporary theory of family planning. The study finds that Ludhiānvī in ​​his "Tibyān al-Furqān" has presented the solution of these problems in a very beautiful and comprehensive way.
Keywords: Tafsīr; Ludhiānvī; social issues